2013
DOI: 10.1002/jmri.24511
|View full text |Cite
|
Sign up to set email alerts
|

T2‐weighted prostate MRI at 7 tesla using a simplified external transmit‐receive coil array: Correlation with radical prostatectomy findings in two prostate cancer patients

Abstract: We have demonstrated feasibility of a simplified external coil array for high-resolution T2-weighted prostate MRI at 7T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…However, a 3T vs. 7T comparison with identical coils would favor one of the field strengths, as optimal coil design depends on the field strength. In this study, the 7T coil array was an in‐house developed array that resulted from a gradual evolution of body imaging arrays at 7T . The 3T coil array is a widely used, state‐of‐the‐art commercial coil and it is also the coil array that is used for prostate cancer patients in our department.…”
Section: Discussionmentioning
confidence: 99%
“…However, a 3T vs. 7T comparison with identical coils would favor one of the field strengths, as optimal coil design depends on the field strength. In this study, the 7T coil array was an in‐house developed array that resulted from a gradual evolution of body imaging arrays at 7T . The 3T coil array is a widely used, state‐of‐the‐art commercial coil and it is also the coil array that is used for prostate cancer patients in our department.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations of MRI are that highfieldstrength MRI systems cur rently available are not configured for intraoperative imaging and surgical guidance, and their resolution is still limited to about 200 μm per voxel in plane and 2-3 mm in the z direction. Future trends in imaging of the prostate using MRI include the introduction of magnets with a higher field strength (for example, 7 T and greater) for continued improvement in sensitivity, resolution, and image acquisition times; [91][92][93][94] however, further safety studies are w arranted before increased field strengths should be used. …”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Rosenkrantz et al demonstrated the feasibility of 7T MRI in 2 patients with biopsy proven prostate cancer. They demonstrated a signal to noise ratio gain of 2.1 at 7T MRI vs 3T MRI and images showed excellent visual correlation with the radical prostatectomy specimens [25]. Several studies demonstrated the safety and feasibility of MR spectrocopic imaging at 7T in patients with biopsy proven prostate cancer.…”
Section: Imaging For Patient Selectionmentioning
confidence: 99%